2018
DOI: 10.3390/en11051132
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Pore-Scale Simulation of Oil Reservoirs

Abstract: Abstract:At the high water cut stage, the residual oil in a reservoir becomes complex and dispersed. Moreover, it is challenging to achieve good predictions of the movement of oil and water in a reservoir according to the macroscopic models based on the statistic parameters of this scenario. However, pore-scale simulation technology based on directly tracking the interaction among different phases can make an accurate prediction of the fluid distribution in the pore space, which is highly important in the impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 81 publications
0
9
0
Order By: Relevance
“…In work [31], the authors rightly state that flooding technology is an important measure for increasing the recovery of crude oil in oil fields. In this paper, the authors used the direct numerical simulation (DNS) method, which is based on the Navier-Stokes equation and the fluid volume (VOF) method, to investigate the dynamic behavior of oil-water flow in a low-permeability pore structure [32,33]. On the basis of the results obtained from the research, the authors concluded that the variability in the non-uniformity of the viscosity action results from the difference in the viscosity of oil and water.…”
Section: A Short Review Of the Contributions In This Issuementioning
confidence: 99%
“…In work [31], the authors rightly state that flooding technology is an important measure for increasing the recovery of crude oil in oil fields. In this paper, the authors used the direct numerical simulation (DNS) method, which is based on the Navier-Stokes equation and the fluid volume (VOF) method, to investigate the dynamic behavior of oil-water flow in a low-permeability pore structure [32,33]. On the basis of the results obtained from the research, the authors concluded that the variability in the non-uniformity of the viscosity action results from the difference in the viscosity of oil and water.…”
Section: A Short Review Of the Contributions In This Issuementioning
confidence: 99%
“…In the special case when gas is at rest, we can observe the motion of the particle-induced by different surface inequalities-this kind of motion is called "phoretic motion" in the literature [68,69]. In general, any nano-particle immersed in the fluid can simultaneously undergo five kinds of motions [70,71].…”
Section: Phenomenamentioning
confidence: 99%
“…The investigation of the flow dynamic characteristic oil-water two-phase flow within porous media at the pore-scale in depth is of great significance to understand the macroscopic phenomenon of the water flooding development process. The pore-scale investigation of multiphase flow behavior and the dynamic process within reservoir rock contributes to clarify the underlying dynamic mechanisms of certain macroscopic water flooding phenomena [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%